LEGITIMASI SOSIAL DAN PERSAINGAN KELUARGA POLITIK DI KABUPATEN NAGAN RAYA, ACEH (2002-2024) - Mauza Farah Yuriko Terazono (MIMBAR : Jurnal Sosial dan Pembangunan, 2026)
This study examines how social legitimacy is constructed, contested, and reconstructed by two competing political families in Nagan Raya Regency, Aceh, across four electoral cycles (2002–2024). Background: Decentralization opened new arenas for local elite competition, yet the ideational and narrative dimensions sustaining dynastic legitimacy remain underexplored. Purpose: To analyze mechanisms of social legitimacy construction and the dynamics of inter-dynastic competition in shaping electoral preferences. Methods: Qualitative interpretive approach with critical discourse analysis; data gathered via in-depth interviews, campaign documents, media archives, and KIP Nagan Raya electoral data (2006–2024). Results: Legitimacy was constructed through three collective social narrative typologies—collective pride (2002–2012), dominance normalization (2012–2017), and anti-dynasty transformation (2017–2022)—followed by a restorative re-narrative in 2024. Conclusion: Multilayered symbolic capital rooted in genealogy, development memory, and communal identity demonstrated electoral durability beyond a single defeat. Implications: Post-decentralization local competition is fundamentally a contest over narrative legitimacy; institutional reforms must address structural conditions enabling dynastic narrative reproduction.